English as a Second Language Acquisition in 8-Year-Olds through YouTube Media - Santoso, Dwi; Mawaddah, Suci (CV. Tripe Konsultan, 2025)
This research article discussed the acquisition of English as a second language in 8-year-old children through YouTube media. This research used a qualitative method with a descriptive approach. The research subjects were an 8-year-old child named Afnan, and his mother, Rantika. Data collection techniques included observation, non-formal interview, and library research. The results showed that; 1) Afnan's second language acquisition process is almost the same as his first language acquisition process. 2) YouTube is proven to promote language development, cross-cultural learning, and motivation in an authentic second language learning environment. Through the medium of YouTube, Afnan is able to communicate in English after being exposed to English channels since the age of 2 years old. His mother deliberately introduced English to Afnan because she believes that it is important to master English from an early age. Therefore, this study also highlights the importance of second language acquisition during the golden age of children, where human absorption and memory are more optimal.